The modulatory role of extrinsic motivation in the relationship between fear of failure and student engagement - Nakhla, Ghada (Journal of University Teaching and Learning Practice, 2025)
Teachers often employ various techniques to motivate and engage students. They may choose to use positive fear appeals as a motivational tactic to stimulate fear that will result in students making greater efforts to avoid failure or they may employ extrinsic incentives to engage students. This study examined the modulatory role of extrinsic motivation, as a differentiated construct, in the relationship between fear of failure and student engagement. Data were collected using self-reported instruments and analysed using moderation and mediation analyses. Extending the motivation literature, this study, sheds new light on the positive modulatory role of extrinsic motivation regulations in the relationship between fear of failure and student engagement. Contributions to practice are implied; there is a need for educators to understand the role of self-imposed and self-endorsed behaviours in influencing engagement among students with high and low fear of failure. Comprehending the complexity of the learning environment in light of the complex nature of human behaviours is considered essential to improving teaching and learning.